Technical and Economic Challenges and Future Prospects of a Smart Grid - A Case Study - Haque, Abrarul; Hussain, Md. Naeem; Ali, Md. Sumon; Khan, Md. Yakub Ali; Halim, Md Abdul (Peneliti Teknologi Teknik Indonesia, 2023)
In order to improve grid efficiency, dependability, and sustainability, smart grid technology is being developed and implemented at the vanguard of updating the world's electrical infrastructure. In addition to looking at the potential implications of smart grid technology, this case study analyzes the technical and financial difficulties encountered during the implementation of a smart grid. Technical issues with energy management and system stability arise when intermittent renewable energy sources are integrated into the smart grid. To make smooth transmission, sophisticated algorithms and grid management strategies are needed. Maintaining data security and privacy is crucial since smart grids mostly depend on digital technology and data exchange. It is a constant worry to defend the grid from hackers and illegal access. The installation of sensors, smart meters, and communication equipment might come with a significant initial cost when implementing a smart grid. One of the main economic challenges is financing these developments while maintaining reasonable power bills. It may be difficult to strike a balance between the interests of technology suppliers, customers, and utilities. Real-time monitoring and control are made possible by smart grids, which improve energy distribution and minimize energy waste. In addition to lowering greenhouse gas emissions, this improves overall energy efficiency. Smart grids can enable EV charging infrastructure as electric vehicle (EV) use increases, providing potential for grid optimization and new income streams for utilities. Reliability could be increased and downtime is decreased in a smart grid when defects can be promptly identified and isolated. The implementation of a smart grid is not without its technical and financial difficulties, but the future seems bright. Overcoming these obstacles may result in an electrical grid that is more sustainable, robust, and profitable for customers as well as utilities. Stakeholder cooperation, flexible regulations, and continuous technical development are needed to address these problems. By providing practical applications and real-world insights into the implementation of a smart grid, the case study acts as a link between theoretical concepts. Stakeholders obtain a comprehensive comprehension of the intricacies involved by analyzing technical and economic obstacles. To maximize the potential of smart grid technology, this knowledge is essential for fine-tuning strategies and creating focused solutions.